An evaluation of the bacteriostatic effect of platelet‐rich plasma. Issue 4 (21st January 2021) - Smith, Oliver J.; Wicaksana, Aditya; Davidson, Donald; Spratt, David; Mosahebi, Ash
Abstract: Chronic wounds are a considerable health burden with high morbidity and poor rates of healing. Colonisation of chronic wounds by bacteria can be a significant factor in their poor healing rate. These bacteria can develop antibiotic resistance over time and can lead to wound infections, systemic illness, and occasionally amputation. When a large number of micro‐organisms colonise wounds, they can lead to biofilm formation, which are self‐perpetuating colonies of bacteria closed within an extracellular matrix, which are poorly penetrated by antibiotics. Platelet‐rich plasma (PRP) is an autologous blood product rich in growth factors and cytokines that are involved in an inflammatory response. PRP can be injected or applied to a wound as a topical gel, and there is some interest regarding its antimicrobial properties and whether this can improve wound healing. This study aimed to evaluate the in vitro bacteriostatic effect of PRP. PRP was collected from healthy volunteers and processed into two preparations: activated PRP—activated with calcium chloride and ethanol; inactivated PRP. The activity of each preparation against Staphylococcus aureus and Staphylococcus epidermis was evaluated against a control by three experiments: bacterial kill assay to assess planktonic bacterial growth; plate colony assay to assess bacterial colony growth; and colony biofilm assay to assess biofilm growth. Compared with control, both preparations of PRP significantly inhibited growth of planktonic S aureus and S epidermis . Activated PRP reduced planktonic bacterial concentration more than inactivated PRP in both bacteria. Both PRP preparations significantly reduced bacterial colony counts for both bacteria when compared with control; however, there was no difference between the two. There was no difference found between biofilm growth in either PRP against control or against the other preparation. This study demonstrates that PRP does have an inhibitory effect on the growth of common wound pathogens. Activation may be an important factor in increasing the antimicrobial effect of PRP. However, we did not find evidence of an effect against more complex bacterial colonies.